THE NUCLEAR TABOO AND THE INTERNATIONAL CAMPAIGN TO ABOLISH NUCLEAR WEAPONS - Bolton, Matthew (Revista de Direito Brasileira, 2019)
This article uses Mary Douglas’ landmark theorization of purity and danger to explore the development of the ‘nuclear taboo’ and ICAN’s creative manipulation of discourses of nuclear pollution. ICAN placed people who had long been marginalized by nuclear diplomacy – survivors, women, indigenous people, civilians, representatives of small states – at the center of the conversation about nuclear weapons. In doing so, ICAN deconstructed discourses legitimating nuclear weapons, revealing the ambivalence and fear underneath diplomatic euphemism. ICAN also turned the stigma associated with nuclear weapons onto those who defended them. I conclude by reflecting on the importance in being transparent about how pariah status for a weapon is socially constructed. Openly discussing the process of stigmatization need not undermine or delegitimize it. Rather, seeing pariah status as a political process enables us to have a conversation about how to address threats to human security without resorting to coercive control.